Cerebral MRI and Clinical Findings in Children with PTEN Hamartoma Tumor Syndrome: Can Cerebral MRI Scan Help to Establish an Earlier Diagnosis of PHTS in Children? - Plamper, Michaela; Born, Mark; Gohlke, Bettina; Schreiner, Felix; Schulte, Sandra; Splittstößer, Vera; Wölfle, Joachim (Cells, 2020)
BACKGROUND: PTEN Hamartoma Tumor Syndrome (PHTS) is caused by germline autosomal-dominant mutations of the tumor suppressor gene PTEN. Subjects harbour an increased risk for tumor development, with thyroid carcinoma occurring in young children. Establishing a diagnosis is challenging, since not all children fulfill diagnostic criteria established for adults. Macrocephaly is a common feature in childhood, with cerebral MRI being part of its diagnostic workup. We asked whether distinct cMRI features might facilitate an earlier diagnosis. METHODS: We retrospectively studied radiological and clinical data of pediatric patients who were presented in our hospital between 2013 and 2019 in whom PTEN gene mutations were identified. RESULTS: We included 27 pediatric patients (18 male) in the analysis. All patients were macrocephalic. Of these, 19 patients had received at least one cMRI scan. In 18 subjects variations were detected: enlarged perivascular spaces (EPVS; in 18), white matter abnormalities (in seven) and less frequently additional pathologies. Intellectual ability was variable. Most patients exhibited developmental delay in motor skills, but normal intelligence. CONCLUSION: cMRI elucidates EPVS and white matter abnormalities in a high prevalence in children with PHTS and might therefore aid as a diagnostic feature to establish an earlier diagnosis of PHTS in childhood.
CRIS-Team Scopus Importer:2020-07-24
Keywords: children; cMRI; enlarged perivascular spaces; macrocephaly; PHTS; PTEN; Virchow–Robin spaces; white matter abnormalities